Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska
Wydawnictwo:Nowa Era
Rok wydania:2015
Rozwiąż równanie 4.2 gwiazdek na podstawie 5 opinii

`a)` 

`(2x-1)^2=(2x+3)^2` 

`4x^2-4x+1=4x^2+12x+9\ \ \ |-4x^2` 

`-4x+1=12x+9\ \ \ |-12x` 

`-16x+1=9\ \ \ |-1` 

`-16x=8\ \ \ |:(-16)` 

`x=-1/2` 

 

 

`b)` 

`(3x+2)^2=(3x-4)(3x+4)` 

`9x^2+12x+4=9x^2-16\ \ \ |-9x^2` 

`12x+4=-16\ \ \ |-4` 

`12x=-20\ \ \ |:12` 

`x=-20/12` 

`x=-5/3` 

 

 

`c)` 

`(3x+1)^2+(4x+1)^2=(5x+1)^2` 

`(9x^2+6x+1)+(16x^2+8x+1)=25x^2+10x+1` 

`9x^2+6x+1+16x^2+8x+1=25x^2+10x+1` 

`25x^2+14x+2=25x^2+10x+1\ \ \ |-25x^2` 

`14x+2=10x+1\ \ \ |-10x` 

`4x+2=1\ \ \ |-2` 

`4x=-1\ \ \ |:4` 

`x=-1/4` 

 

 

`d)` 

`(sqrt2x-2)^2-2(x-1)^2=4x` 

`2x^2-4sqrt2x+4-2(x^2-2x+1)=4x` 

`2x^2-4sqrt2x+4-2x^2+4x-2=4x` 

`4x-4sqrt2x+2=4x\ \ \ |-4x` 

`-4sqrt2x+2=0\ \ \ |-2` 

`-4sqrt2x=-2\ \ \ |:(-4sqrt2)` 

`x=2/(4sqrt2)` 

`x=1/(2sqrt2)` 

`x=(sqrt2)/(2sqrt2*sqrt2)` 

`x=(sqrt2)/(2*2)` 

`x=sqrt2/4`